2018
DOI: 10.1590/1807-1929/agriambi.v22n9p597-603
|View full text |Cite
|
Sign up to set email alerts
|

Do the application forms and doses of boron affect wheat crops?

Abstract: Boron is one of the most limiting micronutrients in the grain production system in Brazil. Thus, the objective of this study was to evaluate the effects of the application forms and doses of boron on the concentration of this nutrient in the leaves, straw, and grains of wheat, as well as the production components and grain yield. The residual effect of boron in the soil was also evaluated. An experiment was conducted in a no-tillage system in Oxisol with clay texture in Selvíria, Mato Grosso do Sul. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Tahir et al (2009) também verificaram rendimento superior de trigo com a aplicação foliar de B, mas em solo com teor baixo do micronutriente. Galindo et al (2018a) também verificaram resultado positivo no rendimento da cultura do trigo com o aumento da dose de adubo boratado até a dose de 2 kg ha -1 , dose recomendada ao final do estudo para essa cultura. Estudos relataram sintomas da deficiência de B em trigo independentemente do teor de B extraído do solo (KATAKI et al, 2002;RASHID et al, 2002), e em estudo com diferentes doses e formas de aplicação de B em trigo, Galindo et al (2018b) demonstraram que, mesmo em solos com boas reservas do micronutriente, a adubação boratada pode aumentar o rendimento da cultura, pois, além da maior demanda de B para a formação das sementes que para o desenvolvimento vegetativo da planta, em solos tropicais é menor a presença de matéria orgânica, grande fonte do micronutriente.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Tahir et al (2009) também verificaram rendimento superior de trigo com a aplicação foliar de B, mas em solo com teor baixo do micronutriente. Galindo et al (2018a) também verificaram resultado positivo no rendimento da cultura do trigo com o aumento da dose de adubo boratado até a dose de 2 kg ha -1 , dose recomendada ao final do estudo para essa cultura. Estudos relataram sintomas da deficiência de B em trigo independentemente do teor de B extraído do solo (KATAKI et al, 2002;RASHID et al, 2002), e em estudo com diferentes doses e formas de aplicação de B em trigo, Galindo et al (2018b) demonstraram que, mesmo em solos com boas reservas do micronutriente, a adubação boratada pode aumentar o rendimento da cultura, pois, além da maior demanda de B para a formação das sementes que para o desenvolvimento vegetativo da planta, em solos tropicais é menor a presença de matéria orgânica, grande fonte do micronutriente.…”
Section: Resultsunclassified
“…Diversas formas de boro podem ser encontradas no solo, com distintas disponibilidades para as plantas, sendo seus teores na solução controlados, principalmente, por reações de adsorção dependentes do pH do solo, do teor de Al (SANTOS et al, 2020) e de matéria orgânica (LEMARCHAND et al,. 2005) O B é um dos micronutrientes que mais limita a produção de grãos nos sistemas agrícolas brasileiros (GALINDO et al, 2018a). No campo, a reprodução das plantas é afetada por baixos teores de B e reduções significativas de rendimento de grãos podem ocorrer sem sintomas visuais perceptíveis durante o crescimento vegetativo, sendo o teor adequado para o desenvolvimento das culturas bastante variável (MARSCHNER, 2012).…”
Section: Introductionunclassified
“…These authors also concluded that the response to boron fertilization is higher in soils with low organic matter content. Galindo et al (2018), working with four boron doses (0, 1, 2, and 4 kg ha -1 ) and boric acid as a source in the wheat crop, found that the application of 2 kg ha -1 of boron in the sowing furrow resulted in higher grain yield. Kappes et al (2008), studying the effects of foliar fertilization with different boron doses (0, 0.1, 0.2, 0.3, and 0.4 kg ha -1 ), found no significant impact of the application of this micronutrient on grain yield of the soybean crop.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of boron in the fruit tissues of loquat increased with the application of borax (Figures 2-4). Similarly, the boron concentration in grains of wheat [59], rice [60], and sunflower tops [61] also increased with the application of boron in a dose-dependent manner. The concentration of Ni in the leaves and fruit pulp of loquat reduced with a change in maturity (Figures 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Before each analysis, the instrument was tuned for daily performance using Agilent 7700X Sensitivity Detection Limit Solution, Agilent, USA. This is an aqueous multi-element standard solution of Li, Y, Co, Ce, and Tl for consistent sensitivity ( 7 Li, 59 Co, 89 Y, 140 Ce, 205 Tl) and minimum doubly charged and oxide species levels ( 140 Ce). The concentration of elements in the solution was 10 µg L −1 .…”
Section: Instrumentation and Reagentsmentioning
confidence: 99%